Stative and Dynamic Predicates in Writing Descriptive Text Students’ Assignments: A Semantic Study - MUHAMMAD SAIBANI WIYANTO; IRA NOVINDA; FITRI RESTI WAHYUNIARTI (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research investigates how stative and dynamic predicates are used in descriptive writing. Previous research has focused on the syntactic and semantic aspects of these predicates in various languages and literary forms, such as English poem andCorona Virus Songs. However, research on their application in descriptive writing is still rare. The purpose of this study is to examine how students use stative and dynamic predicates in their descriptive texts. This study was conducted on grade VIIIstudents at SMPK Jombang, using a qualitative descriptive approach and the classification of stative and dynamic verbs from the works of (Saeed, 2003) and (Ghubin, 2021). Through this analysis, the researcher aims to explore the frequency andnature of the use of stative and dynamic verbs in students' descriptive text assignments. The findings show that stative verbs are used more frequently than dynamic verbs in students' writing, which suggests a preference for stative verbs in their descriptive writing.